Key Role of Image Guided Fine Needle Aspiration Cytology in Diagnosing Intra-Abdominal Lesions - Kolla, Sireesha; Inuganti, Renuka Venkata; B, Chaitra; Vaddatti, Tejeswini (Annals of Pathology and Laboratory Medicine, 2020)
Background: Masses in the abdominal cavity are often deep, non-palpable and palpable at times which can be inflammatory, benign or malignant. With increased sophistication of radiologic imaging techniques these deep seated lesions are detected more frequently and confirmed tissue diagnosis is essential for both planning of treatment and staging in case of malignant lesions. Image guided aspiration is an effective way to obtain diagnostic material and avoid diagnostic laparotomy. This study was conducted to categorize various intra-abdominal lesions according to their site of involvement, study their cytomorphological features, and classify them as benign, malignant and inflammatory and assess the utility of image-guided cytology in the diagnosis of intra-abdominal lesions. Methods: This cross sectional study approved was done on image guided fine needle aspiration cytology smears of intra-abdominal masses. Age, sex and site details were retrieved from the archives. Hematoxylin and Eosin stained smears were reviewed by the Cytopathologist and diagnosis was arrived at after correlating with clinical and radiological data. Core biopsy or excision biopsy of the available cases were also reviewed and checked for correlation. Result: A total of 120 cases were studied with age ranging from 18-81years, 30% of patients were in the 61-70 years age group, followed by 27% cases in 51-60 years age group and 20% cases in 41-50 years age group. The male to female ratio was 1.03:1. 62.5% of cases were from hepatobiliary region, followed by 17.5% cases from pancreatic masses and 11 cases (9.16%) from ovarian masses. 80% cases were malignant, 10% were inflammatory cases, 9.2% cases were inconclusive and 1 (0.8) benign lesion. Among the malignant lesions primary malignancies (Hepatocellular carcinomas and Adenocarcinomas) were more common than secondary deposits. This study showed 88.9% sensitivity, 83.3% specificity and 87.5% of diagnostic accuracy. Conclusion: Image guided aspiration of intra-abdominal lesion is a simple, economical, less complicated and less time consuming procedure that differentiates between malignant and non malignant conditions with high accuracy and can be used as pre-operative diagnostic procedure for planning further management of patient.